Growth optimization procedures for the phytopathogen Xylella fastidiosa - Campanharo, J. C.; Lemos, MVF; Lemos, EGD (Springer, 2003)
For the first time, growth curves are shown for the phytopathogen Xylella fastidiosa on traditional growth media such as PW (periwinkle wilt), BCYE (buffered charcoal yeast extract), and on new ones such as GYE (glutamate yeast extract) and PYE (phosphate yeast extract) that were developed in this work. The optimal growth conditions on solid and liquid media as well as their measurements are presented, by using total protein content and turbidity determinations. The results demonstrated that yeast extract provided sufficient nutrients for X. fastidiosa, since the cells grew well on PYE medium.